A SECURE ZONE BASED CLUSTERING PROTOCOL [ZBCP] FOR MOBILE AD HOC NETWORKS [MANETs] - Gayathri, K. (IJRDO -Journal of Computer Science Engineering, 2016)
Mobile Ad Hoc Networks (MANETs)are described as a collection of multi hopwireless mobile nodes, infrastructure lessconnectivity and dynamic topology innature. Designing a secure protocol forMobile Ad Hoc Network is a challengingtask. There are many protocols proposed forsecure routing in MANETs In this thesis, weproposed a Zone Based Clustering Protocol[ZBCP] which is a hybrid routing protocoland it is a grouping of both proactive andreactive routing technique in MANETs. Theimplementation of proposed protocol isbased on the clustering technique in ZoneBased Routing [ZBR]. Routing Disorder[RD] attack is the major issue in ZoneBased Routing [ZBR], the Secure ZoneBased Clustering Protocol [ZBCP] canprovide a basis for the securecommunication between mobile nodes.